Fund-level FX hedging redux - Leonie Bräuer; Harald Hau (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2024)
Over the past decade, European investment funds have substantially increased their investment in dollar-denominated assets to more than 3.8 USD trillion, which should give raise to substantial currency hedging if US investor have reciprical currency exposures in their international portfolios. Using comprehensive new contract level data (EMIR) for the period 2019-2023, we explore how the FX derivative trading by European funds compares to a feasible theoretical benchmark of optimal hedging. We find that hedging behavior by all fund types is often partial, unitary (i.e., with a single currency focus), and sub-optimal. Overall, the observed FX derivative trading does not significantly reduce the return risk of the average European investment funds, even though optimal hedging strategies could without incurring substantial trading costs.
Keywords: E44; F31; F32; G11; G15; G23; 330; Global Currency Hedging; Institutional Investors; Mean-Variance Optimization